REVIEW ON BREAST CANCER AND ITS TREATMENT - Gontla Charishma, Gontla Charishma; Polisetty Navya Kusuma, Polisetty Navya Kusuma; J.Bhargava Narendra, J.Bhargava Narendra (International Journal of Indigenous Herbs and Drugs, 2020)
Breast cancer is the second leading cause of cancer death in women. In breast cancer the cells are increased abnormally. Early diagnosis of breast cancer is the best method for the cure or taking treatment to this disease. In some countries the breast cancer patient’s survival rate is more than above 80% due to early prevention. Increased public awareness and improved screening thier diagnosis at stages amenable to complete surgical resection and curative therapies.This disease effects physical, mental and social aspects of women life .This article gives information about and overview of breast cancer and its treatment.